SEVERAL PILLARS OF HEALTH TRANSFORMATION IN INDONESIA: FROM RESILIENCE PHARMACEUTICAL SUPPLY, HEALTH INSURANCE, PRIMARY HEATH CARE, TO DIGITAL HEALTH - Nur Atika (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2023)
Indonesian Government is currently focusing on several efforts to accelerate the achievement of health goals through the implementation of health transformation initiatives. In November 2022, the Indonesian Minister of Heath announced six pillars for health transformation, which are: (1) transformation of primary service; (2) transformation of referral service; (3) health resilience system transformation; (4) transformation of health financing system; (5) health human resources transformation; (6) transformation of health technology.